Music by Claude Debussy and Maurice Ravel: a Modern View of the Problem of Style Identification - Zharkova, Valeriya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the article is determined by the appeal to the debatable issues of stylistic differentiation of the works by Claude Debussy and Maurice Ravel as the French musical culture leading representatives of the late 19th and the first third of the 20th centuries. The research reflections about the connections betwen Debussy and Ravel on the principle “for / against” have not subsided for more than a hundred years. This testifies to the special urgency of this problem and the need to search for modern approaches to understanding the artistic identity of two brilliant contemporaries. Scientific novelty. For the first time, the multidirectionality of the composing strategies by Debussy and Ravel is indicated through the the concept of style in its interdisciplinary philosophicalcategorical status and the explanationof its functions of identification and communication in the general cultural understanding (O. Ustyugova). For the first time the difference between the cultural phenomena processes integration in the era of modernism into the new artistic wholes, with unique properties, which is appropriate to define as “Debussy’s style” and “Ravel’s style”, is revealed. The purpose of the article is to reveal the multidirectionality of the composing strategies of Debussy and Ravel through an appeal to the main stylistic functions of identification and communication in general cultural understanding (O. Ustyugova); to designate the non-coincidence of channels of integration of cultural phenomena in the era of modernism into new artistic wholes, which have unique properties such as “Debussy’s style” and “Ravel’s style”. The research methodology includes the use of historical, stylistic, comparative methods. Main results and conclusions. The existing musicological literature emphasizes the influence of romanticism, post-romanticism, impressionism, symbolism, neoclassicism, Art Nouveau, moderne style on the formation of the individual style of Debussy and Ravel. Each of these directions had a certain reflection in the work of composers. However, let us try to highlight in the conceptual space of the many-sided “isms” of the cultural context of the era of modernism the hidden sources of the deployment of the creative intentions of the both brilliant contemporaries. We will choose the fundamental work of E. Ustyugova “Style and Culture: Experience of Building a General Theory of Style” (2003) as a methodological basis for this. E. Ustyugova proposes to go beyond the understanding style as a “migratory structure” (term by J. Rebane) and a convenient “classification tool” (J. Burnham) in structural and typological studies of art and move on to a comprehensive study of the essence of this phenomenon. For this, according to the researcher, it is necessary to carry out two analytical procedures. The first is based on the awareness of the experience of the mismatch between the object and the subject. The second involves considering the style in the aspect of intersubjective communication. With this view on the problem of identifying the patterns of formation and development of cultural phenomena, it is not the nominative parameters and the “herbarization” of genrelinguistic units that come to the fore, but the comprehension of the multilevel subject-object relations that formed these phenomena; “live reproduction” of the matrix of the world perception as channels of communication between the “I” and everything that appears as “not-I”. The creative paths of Debussy and Ravel represent diferent creative strategies. The “pure meaning”, unspeakable by words and free from all earthly, to which Debussy aspired, creates parallels with the texts of symbolist poets and destroy the boundaries between “I” and “not-I”. In the fundamental monographs of French researchers dedicated to the composer an idea has long been entrenched: the composer’s creative laboratory was poetry, and Debussy’s address to the poetic word throughout all his creative decades constantly expanding the semantic horizons of his “artistic realities”. Debussy’s spiritual intentions merged into a single sound-glow in the indivisible space of being. The word in all its dimensions (from literal to metaphysical) indicated the stages of the process of dissolving the personal “I” and going beyond (au-délà) the established forms of artistic expression. Therefore, various kinds of the names (or “afterwords”, as in the Preludes), epigraphs, numerous super-detailed directions remained an integral part of an integral sound structure. His musical language, destroying the connections in time between the past and the future (rejection of the system of functional gravities that should be “stretched” in musical memory), created a certain correspondence (“here and now”) with the phenomenon of being. Hence the following characteristics of the composer’s musical works: 1) the impeccable construction of the whole, which is “thought out to the smallest detail” (E. Denisov), subtle multilevel “correspondences” and symmetries; 2) total thematization of texture (K. Zenkin); 3) selfsufficient semantic expressiveness of the “pure sound forms” (K. Zenkin), which became the embodiment of “an agonizing thirst for undeniably pure” (S. Velikovsky). These properties of Debussy’s style open up the possibility to get into the spiritual dimensions filled with pure beauty, which so attracted the followers of Baudelaire. Using the typology of teh subject-object relations proposed by E. Ustyugova, Debussy’s style can be attributed throughout the paradigm of hidden subjectivity. Debussy was well aware of his “non-romantic” position. The artistic aspirations of Maurice Ravel more clearly resonate with the creative attitudes of Art Nouveau artists, who were looking for new forms of plastic expressiveness mainly in spatial forms of art. It seems that it is with this direction that a special feeling of the plasticity of the musical material and the entire musical composition as a unique phenomenon is associated, which determines the composer’s creative credo. The concept of “plasticity” indicates such a connection between coordinated phenomena, which appears through the reincarnation (transformation) of a certain material substance, when we keep in memory its output characteristics. Ballet works and the reliance on dance genres (and more broadly, various types of plasticity of gesture and movement) reveal the hidden basis of the composer’s thinking. This approach allows one to re-evaluate Ravel’s connections with the ancient heritage (it is symptomatic that the composer called his first “adult” work, devoted to the press, “Antique Minuet”) and to understand the meanings of constant antique reminiscences with which he filled his life. Like a real dandy who lets the vibrations of the world pass through himself, Ravel is sensitive to them and “cuts off” random, “ugly”, “unnecessary” ones. Hence — the special beauty of the artistic structures created by the composer. They are built not in a “filtered” ideal-beautiful dimension, but in the space of shimmering opposites (the corporeal — free from the corporeal, the familiar — the unknown). Ravel’s inherent tendency towards the graphic relief of the melodic line creates parallels with the “famous lines of Art Nouveau” (Fahr-Becker Gabriele) and is especially distinct, characterizes the composer’s later works. The non-everyday register of semantic reverberations of what is happening in the process of metamorphosis in the composer’s music (his plastic questioning about the existential nature of the source material) demanded a special listener’s responsiveness. Mistifications, hiding behind a mask, playing with the listener are Ravel’s usual communication strategies. Therefore, according to the typology of the subject-object relations proposed by E. Ustyugova, we can speak here of the paradigm of “open subjectivity”, which is characterized by the direct orientation of the subject towards himself. Hence — the principle of auto-citation characteristic of Ravel. The quintessence of its use are the composer’s later works — the opera Child and Magic, as well as the Piano Concerto in G major — the Dandy summa summarum of the composer’s previous career. The game of “correspondences” (Baudelaire) was manifested by composers in various ways and conditioned various channels of communication. Debussy makes the semantics of sound education a semantic unit, appeals to the listener with the expressiveness of the structure itself. Therefore he always emphasizes, appeals to the elite listener. Ravel, on the other hand, hides behind masks and theatrical illusions. He needs a listener who has a culture of distance (who owns wide meaning contextual fields). The contextual layers associated with musical texts express that “degree of distance” from the object of attention, which the composer himself chooses and whose parameters are constantly changing. Therefore, Ravel never turns twice in the genre, style or stylistic model he has already used. So, if the works by Debussy can be perceived “from scratch” because of their structural completeness and semantic tightness, then the works by Ravel require the listener to know the musical context and readiness to lay it out “fold by fold” (J. Deleuze) in new semantic projections. At the turn of the 19th and 20th centuries, French culture was looking for a means of creating a “state of resonance” (G. Bachelard) as an extraordinary impression, “awakening”, without which a person cannot take place. Debussy and Ravel moved in this direction. Therefore, only through the identification of all the “correspondences” of the era of a total change of creative guidelines and a departure from unambiguous stylistic “avatars” can one feel its essential discoveries. The study of the lines of intersection of the Debussy music and the Ravel music with various artistic phenomena of the past and the present illuminates certain reflections of the “style of the era”. However understanding the deep patterns of the creative manner of the two contemporaries requires differentiating the definitions of “Debussy’s style” and “Ravel’s style” and their further studying.